Molecular bioinformatic and functional analysis of Enolase4 gene during siphonal autotomy and regeneration of razor clam Solen grandis - Zhidong Zhang; Xuefeng Sun; Aihua Chen; Jiaxin Yang; Suhua Chen; Yu Zhang; Yi Cao; Yuheng Peng; Yanqing Zhu; Yangping Wu (Frontiers in Marine Science, 2023)
For the razor clam Solen grandis , siphonal autotomy and regeneration is a necessary means of facing external stress, which is accompanied by a large amount of energy consumption. To explore the function of the ENO4 gene in the siphonal autotomy and regeneration of S. grandis , the full-length cDNA of the ENO4 in S. grandis was cloned and characterized. The full-length cDNA of SgENO4 was 2,773 base pairs (bp), with an 1,851 bp coding sequence (CDS) encoding 616 amino acids. ​Bioinformatic analysis revealed a slightly lower codon usage bias and a relatively stable nucleotide composition in the SgENO4 sequence. Three conserved motifs were found from the SgENO4 sequence. These conserved motifs vary in length from 14 to 27 amino acids. Moreover, in the siphonal pre-autotomy of razor clams, expression level of the SgENO4 gene was significantly higher in the hepatopancreas and siphonal base than other tissues ( P < 0.05). However, the expression of the SgENO4 gene in the siphonal base decreased significantly in the siphonal post-autotomy 7 hours and gradually recovered as the regeneration process continued. ​Linear correlation analysis showed that there was a significant linear correlation between specific weight of siphon and relative expression levels of SgENO4 (R 2 = 0.826). RNA interference (RNAi) result showed that the specific weight (the proportion of siphonal weight to body weight) is significantly lower than other groups on the seventh day ( P < 0.05), suggesting that interfering with the expression of the SgENO4 gene could inhibit the siphonal regeneration of S. grandis . These results further demonstrate that SgENO4 is a conserved sequence and that it plays a crucial role in the siphonal autotomy and regeneration of S. grandis , advancing further understanding in exploring molecular mechanisms in the siphonal autotomy and regeneration.